2005
DOI: 10.1074/jbc.m501315200
|View full text |Cite
|
Sign up to set email alerts
|

Coq3 and Coq4 Define a Polypeptide Complex in Yeast Mitochondria for the Biosynthesis of Coenzyme Q

Abstract: Coenzyme Q (Q) is a redox active lipid essential for aerobic respiration in eukaryotes. In Saccharomyces cerevisiae at least eight mitochondrial polypeptides, designated Coq1-Coq8, are required for Q biosynthesis. Here we present physical evidence for a coenzyme Qbiosynthetic polypeptide complex in isolated mitochondria. Separation of digitonin-solubilized mitochondrial extracts in one-and two-dimensional Blue Native PAGE analyses shows that Coq3 and Coq4 polypeptides comigrate as high molecular mass complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
120
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(130 citation statements)
references
References 58 publications
7
120
1
2
Order By: Relevance
“…It was shown that DMQ 6 co-elutes with Coq3 O-methyltransferase activity and high molecular mass Coq polypeptide complexes during size exclusion chromatography of digitonin extracts of mitochondria [18]. Yeast coq7 null mutants cultured in the presence of exogenous Q 6 were able to synthesize DMQ 6 , and steady-state levels of Coq4 polypeptides were restored, indicating that the presence of Q 6 itself may stabilize the Coq polypeptide complexes [23,34].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…It was shown that DMQ 6 co-elutes with Coq3 O-methyltransferase activity and high molecular mass Coq polypeptide complexes during size exclusion chromatography of digitonin extracts of mitochondria [18]. Yeast coq7 null mutants cultured in the presence of exogenous Q 6 were able to synthesize DMQ 6 , and steady-state levels of Coq4 polypeptides were restored, indicating that the presence of Q 6 itself may stabilize the Coq polypeptide complexes [23,34].…”
Section: Introductionmentioning
confidence: 97%
“…The yeast Coq4 and Coq9 polypeptides co-purify with other Coq polypeptides and both migrate at high molecular mass in separation of digitonin extracts of mitochondria [18][19][20][21]. Thus, we used the Coq4 and Coq9 polypeptides as sensitive indicators of the state of the high molecular mass Coq complexes.…”
Section: The Coq4 and Coq9 Polypeptides Are Sensitive Indicators Of Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Gel filtration chromatography shows that Coq3p, Coq4p, Coq6p, and Coq7p coelute as a high-molecular-weight complex (22,28). Coq3p, Coq4p, and Coq7 comigrate as highmolecular-mass complexes as assessed by two-dimensional blue native analysis (22,28).…”
Section: Figmentioning
confidence: 99%
“…E. coli strains harbored plasmids expressing the designated genes as follows: pAHG, UbiG K-12 ; pUbiG THU , UbiG THU ; pHZ1, UbiX THU ; and pPZ2, UbiX K-12 . L-methionine as previously described (22,24). O-methyltransferase activity assays were linearly dependent on time of incubation, substrate concentration, and amount of permeabilized cells.…”
Section: Figmentioning
confidence: 99%